Activated carbon from pyrolysis of brewer's spent grain: Production and adsorption properties. Issue 7 (July 2014) - Vanreppelen, Kenny; Vanderheyden, Sara; Kuppens, Tom; Schreurs, Sonja; Yperman, Jan; Carleer, Robert
Brewer's spent grain is a low cost residue generated by the brewing industry. Its chemical composition (high nitrogen content 4.35 wt.%, fibres, etc.) makes it very useful for the production of added value in situ nitrogenised activated carbon. The composition of brewer's spent grain revealed high amounts of cellulose (20.8 wt.%), hemicellulose (48.78 wt.%) and lignin (11.3 wt.%). The fat, ethanol extractives and ash accounted for 8.17 wt.%, 4.7 wt.% and 3.2 wt.%, respectively. Different activated carbons were produced in a lab-scale pyrolysis/activation reactor by applying several heat and steam activation profiles on brewer's spent grain. Activated carbon yields from 16.1 to 23.6 wt.% with high N-contents (> 2 wt.%) were obtained. The efficiency of the prepared activated carbons for phenol adsorption was studied as a function of different parameters: pH, contact time and carbon dosage relative to two commercial activated carbons. The equilibrium isotherms were described by the non-linear Langmuir and Freundlich models, and the kinetic results were fitted using the pseudo-first-order model and the pseudo-second-order model. The feasibility of an activated carbon production facility (onsite and offsite) that processes brewer's spent grain for different input feeds is evaluated based on a techno-economic model for estimating the net present value. Even though the model assumptions start from a rather pessimistic scenario, encouraging results for a profitable production of activated carbon using brewer's spent grain are obtained.